Work Hard or Play Hard? Degree Class, Student Leadership and Employment Opportunities - Stijn Baert; Dieter Verhaest (Institute of Labor Economics (IZA), 2018)
We investigated the impact on first hiring outcomes of two main curriculum vitae (CV) characteristics by which graduates with a tertiary education degree distinguish themselves from their peers: degree class and extra-curricular activities. These characteristics were randomly assigned to 2,800 fictitious job applications that were sent to real vacancies in Belgium. Academic performance and extra-curricular engagement both enhanced job interview rates by about 7%. The effect of a higher degree class was driven by female (versus male) candidates and candidates with a master's (versus a bachelor's) degree. We did not find evidence for these CV characteristics to be substitutes or to reinforce each other's effect.
Keywords: J23; J24; I23; C93; 330; degree class; extra-curricular activities; hiring; field experiment